Challenges and Prospects of e-Government implementation in Afghanistan. Issue 1 (5th November 2020) - Samsor, Abdul Mateen
Abstract : Purpose: The aim of this study is to identify the challenges and barriers to e-Government set up in developing/conflict countries, related to Information Communication and Technology (ICT) and social obstacles – that are common in developing countries like Afghanistan. In today's world e-Government plays an important role of providing easy access to government services that enable citizens in general to communicate faster. This very research concentrates on the implementation of e-Government challenges in developing countries, particularly in Afghanistan. This paper is covering (1) method of study; (2) research strategy; (3) finding and policy recommendation; (4) limitation; (5) theoretical implication; (6) recommendation and conclusion. Additional data related to e-Government in Afghanistan, acquired via a quantitative survey and interviews can also help this analysis. Design/methodology/approach: This research incorporates both theoretical and empirical study; using both quantitative and qualitative method for data collection. Also, as already noted, the study reviews different literature and academic documents. The original work of the study is the collection of relevant first-hand information for empirical analysis from experts of both public and private institutions such as IT, CIO and management experts through the use of a survey tools. This was done using web-based surveying and delivery of hard and soft copies to the experts to obtain their notions about e-Government implementation obstacles. Finally, both quantitative and qualitative survey results are calculated and presented. Findings: Empirical study has established that 5 obstacles out of 15 named by respondents, stakeholder involvement, with the highest mean, (4.1145), coordination (4.0038), information sharing (3.9962), ICT literacy (3.9822) and e-Government awareness (3.8830) are considered to be the major obstacles. This opinion was also expressed by the respondents to the in-depth interview which was explained in a paper with detail. Research limitations/implications: Most research record numerous limitations, therefore, it is important to note that this study is no exception. Some of the limitations were recorded in the course of the study will be counted for the purpose of placing the finding in the right perspective. The limitations of this study were time constraints and difficult to generate enough participation in the survey. Because of that, I did a quantitative survey but could include very few members of top management. Second, the study is limited due to the lack of participation by respondents from various sectors such as citizens, university students, academia, banks, businesses and NGOs. The third limitation was lack of research materials for this study. Many difficulties were encountered with respect to find materials of previous research studies on the topic and in particularly in the context of Afghanistan. Practical implications: The studies conducted previously on e-Government and referenced herein highlighted implementation challenges in developing countries as a group. Applying this study in Afghanistan may contribute to our understanding of key challenges facing in implementing e-Government process specifically in Afghanistan. The current study contributes some significant findings to the academic field of studying e-Government implementation challenges. It adds the support and information from public and private sector's perspective regarding major challenges in e-Government implementation in Afghanistan. Social implications: As per looking to the experience of developed and developing countries, this study emphasizes the following key initiatives to be performed in parallel with the running projects by Ministry of communication and IT [18]. 1-Pilot projects, 2-Simplification of Business Processes, 3-A strong committed national leadership, 4-Involvement of Stakeholders, 6-To granting incentives for involvement of local ICT companies, 7-Exemption of basic ICT, 8-To develop a standard ICT infrastructure Originality/value: Governments around the world are under the pressure from rapid globalization, fiscal, social and technological changes to provide services that are citizen-centric, efficient, transparent, effective, one stop, any time and nonstop. Post-conflict countries are under even greater pressure to create such services because they replace the vacuum caused by the violence and will be the only services offered, rather than simply an upgrade of current government offerings that already meet citizen needs. The adoption of technology is the most efficient way to integrate the public and private sector and to provide services with accountability, transparency and efficiency, but this is not an easy task, especially for developing countries. This research looks at e-Government implementation challenges in developing countries and particularly in Afghanistan. A literature review shows many challenges common among developing countries: a lack of ICT literacy, incomplete infrastructure, a digital divide existing between the rural poor and the emerging urban middle class, an uncertainty about data privacy and data security, the absence of comprehensive ICT policies and legislation, lack of an ICT culture in government and the traditional components of the economy, questions regarding the government's ongoing financial commitment to the project, e-Government awareness, willingness of ministries to engage in information sharing, a void of ICT leadership outside the technologically oriented ministries, resistance to change, an historic lack of intergovernmental coordination and low stakeholder involvement are just some of the many challenges identified. The author belief that developing countries realize the importance of e-Government and consider the implementation of e-Government to be the critical tool for economic stability and growth as well as developing a more transparent, less corrupt government. The survey questionnaires were developed based on the challenges found in literature review. The survey questionnaire was translated into local languages (Pashto and Dari) and an English version served as control indicator by a professional local translator. At first a pilot version was sent to 10 officials from the Ministry of Communication and IT. After attesting period, the survey was circulated to 150 respondents who were experts in various fields such as CIO, Management and IT in Afghanistan. All respondents agreed that stakeholder involvement, coordination, information sharing, ICT literacy, awareness, resistance to change, ICT, finance issues, ICT policy, leadership, data privacy, legislation, ICT culture and digital divide are some of the major challenges for e-Government implementation in Afghanistan. Respondents (3.1412) on ICT security were impartial in their response on whether to include this indicator into challenges. Many projects are run by the Ministry of Communication and IT and within completion of these projects most of the challenges that identified in the analysis of the quantitative survey will be addressed, although the government is also vigorously pursuing legal and policy modifications. As per looking to the experience of developed and developing countries, this study emphasizes the following key initiatives to be performed in parallel with the running projects by Ministry of communication and IT [18]. Pilot projects should be implemented in two ministries as test beds prior to general roll out to ensure the efficient use of money needed for E-government projects. This will have two benefits from one side it will save money in terms of failing projects as argued by *19+ "E-government in developing countries fail, with 35% being classified as total failures (E-government was not implemented or was implemented but immediately abandoned), and 50% as partial failures (major goals were not attained and/or there were undesirable outcomes)". On the other hand, in case.